1990
DOI: 10.1007/bf03005462
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cross-infection related to the multiple use of disposable syringes

Abstract: The rate of blood contamination of IV tubings used in anaesthesia practice was investigated. Only IV tubings started in the operating room were studied. First, 300 tubings of three different types were tested at the three distal injection sites. The contamination rate was 3.3 per cent at the injection site closest to the IV catheter and 0.3 per cent at the furthest. The presence of a check-valve did not affect the contamination rate. Second, 300 third injection sites fixed at a level equal to or above the IV c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
0
5

Year Published

1997
1997
2019
2019

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 7 publications
0
24
0
5
Order By: Relevance
“…[6][7][8] It has been shown that reusing syringes can be associated with bacterial contamination of its content 12 and, even more worrying, their contamination by occult blood could lead to the transmission of bloodborne viral infection between patients. 13 The use of the same syringe for more than one patient has indeed been identified as a risk factor in many of the reported cases, 2,3,5 has been condemned many times [6][7][8]14 and must be totally abandoned. The implantation of adequate preventive measures does not present a cumbersome task for anesthesiologists and their avoidance cannot be justified by costcontainment reasons or concerns about potential delays of the surgical schedule.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] It has been shown that reusing syringes can be associated with bacterial contamination of its content 12 and, even more worrying, their contamination by occult blood could lead to the transmission of bloodborne viral infection between patients. 13 The use of the same syringe for more than one patient has indeed been identified as a risk factor in many of the reported cases, 2,3,5 has been condemned many times [6][7][8]14 and must be totally abandoned. The implantation of adequate preventive measures does not present a cumbersome task for anesthesiologists and their avoidance cannot be justified by costcontainment reasons or concerns about potential delays of the surgical schedule.…”
mentioning
confidence: 99%
“…[6][7][8] On sait que la réutilisation des seringues peut être associée à la contamination bactérienne de son contenu 12 et, encore plus inquiétant, que leur contamination occulte par du sang peut provoquer la transmission d'infection virale à diffusion hématogène entre les patients. 13 L'usage d'une même seringue pour plus d'un patient a, en effet, été reconnue comme un facteur de risque dans de nombreux cas publiés. 2,3,5 Cette pratique a été condamnée de nombreuses fois [6][7][8]14 et doit être absolument abandonné.…”
unclassified
“…It has been shown that syringes can become contaminated with blood after being in contact with the injection ports of iv tubings. 4 The presence of a check valve in the iv tubing does not prevent blood reflux. Moreover, blood contamination of injection ports frequently cannot be detected by visual inspection.…”
mentioning
confidence: 99%
“…Moreover, blood contamination of injection ports frequently cannot be detected by visual inspection. 4 Finally, it has also been clearly demonstrated that changing the needle was ineffective in preventing contamination of syringes and their contents. 4 Warnings against the practice of reusing syringes have been published in the last ten years, s, 6 Moreover, in 1992, the Committee on Occupational Health of Operating Room Personnel of the ASA published recommendations specifically addressing the practice of anaesthesia.…”
mentioning
confidence: 99%
See 1 more Smart Citation